(untitled) (Damascus University Journal of agriculture sciences, 2021)
This research aimed to determine the relationship between diameter and volume of Pinus trees afforested in Damascus province and its countryside. Breast height diameter and height of tree were measured for more than 500 Cupressus sempervirens L trees. The relationship between diameter and volume was studied, and a model of diameter and volume was developed as a polynomial model represented as follow: V = 0.0011*DBH2 - 0.0157*DBH + 0.1015 Results revealed a strong and significant correlation (r=0.99, p<0.01) between the diameter and the volume of trees, with a high coefficient of determination (R2=0.97).